Two-Year Outcome of Surgery in Glaucoma Patients - Hüppi, Roger; Wagels, Barbara; Todorova, Margarita (Klinische Monatsblätter für Augenheilkunde, 2022)
Purpose To evaluate the 2-year surgical treatment outcome in glaucoma patients.Methods A retrospective, single-center, interventional study was performed on 160 eyes of 125 patients suffering glaucoma, including POAG (82 eyes), pseudoexfoliation (PEX) (59 eyes), pigment dispersion (8 eyes), and secondary glaucoma (2 eyes). Eyes with uncontrolled intraocular pressure (IOP) or signs of glaucoma progression despite medical treatment were included to undergo either trabeculectomy (TE), XEN implantation, combined TE with phacoemulsification (TE + IOL), or XEN implantation with phacoemulsification surgery (XEN + IOL). Primary efficacy outcome was the mean IOP reduction. Secondary outcome was the mean reduction in the number of medications. The data were compared at baseline vs.1 day, 1 week, and 1, 3, 6, 12, and 24 months following surgery. For statistical evaluation, ANOVA-based linear mixed-effects models were performed with SPSS.Results The mean IOP reduction in a 2-year follow-up was 30.31% (22.17 vs. 15.45 mmHg, p < 0.001). The mean number of antiglaucoma medications was reduced from 2.87 to 0.58 (p = 0.001), where TE alone or combined surgeries seemed to be more effective than isolated XEN surgery. Transient IOP hypotony on the first postoperative day occurred in PEX patients following TE surgery (p = 0.024). At 6 months, PEX patients with isolated XEN surgery showed a transient IOP increase, whereas those after combined TE + IOL surgery showed the lowest IOP within the PEX group compared to other glaucoma patients (p < 0.026).Conclusions After 2 years, all performed glaucoma surgeries achieved a significant reduction in IOP and the number of antiglaucoma medications.
Keywords: glaucoma; surgery; minimally invasive glaucoma surgery; trabeculectomy; XEN